Therapeutic efficacy of common anthelmintics used in the control of gastrointestinal nematodes in naturally infected sheep in Bishoftu, Central Ethiopia - Yihenew Getahun Ambaw; Ambachew Motbaynor Wubaye; Melkamu Temesgen Mekonen; Simachew Getaneh Endalamew; Biruh Mebratu Belay; Simegnew Adugna Kallu (Veterinary and Animal Science, 2025)
Nematode parasites are a constraint on animal production and welfare. Anthelmintic resistance (AR) rigorously threatens the possible use of parasite control methods. Hence, this study aimed to assess the anthelmintic use practices of sheep farmers and evaluate the efficacy of common anthelmintics for gastrointestinal nematodes (GINs) in sheep in Bishoftu, Central Ethiopia. A survey was conducted with 100 randomly selected sheep farmers to gather information on anthelmintic use practices. Additionally, 90 nematode-infected sheep were selected for efficacy testing of the treatments. The sheep were chosen if the eggs per gram (EPG) was ≥ 150 in faeces and randomly assigned to three treatment groups (30 animals per group). Group 1, Group 2, and Group 3 were treated with ivermectin, albendazole, and tetramisole, respectively. Faecal samples were collected on days 0 (pretreatment) and 7 and 14 (after treatment). The modified McMaster method was used to count the eggs and fifty multiplication factor to estimate the EPG. The faecal egg count reduction test (FECRT) was utilized to assess the efficacy of the anthelmintics on day 14. The survey revealed that ivermectin was the most regularly (54 %) utilized anthelmintic to treat sheep nematodes, followed by albendazole (28 %) and tetramisole (15 %). The respondents also reported that the choice of anthelmintics was related to the prescription of veterinarians (52 %), color (23 %), affordability of price (14 %), and availability (11 %). The FECRTs on the 14th day were 87.7, 75.7, and 77.0 % for ivermectin, tetramisole, and albendazole, respectively. Although nematodes have developed resistance to all the tested anthelmintics, there was a significant (p < 0.001) reduction in the faecal egg count (RFEC) after treatment. During pretreatment, Hemonchus, Trichostrongylus, Teladorsagia, Cooperia, Trichuris, Bunostomum, Strongyloides, Chabertia, Esophagostomum, and Nematodirus and after treatnment Hemonchus, Trichostrongylus, Teladorsagia, and Trichuris were detected. The results revealed that gastrointestinal nematodes (GINs) in sheep have developed resistance to the tested anthelmintics.